Production of itaconic acid from palm oil mill effluent (POME) using Aspergillus Terreus nrrl 1960 immobilized in PVA-alginate sulfate beads - Ahmad Kamal, Qistina (2013)
Palm Oil Industry is one of the biggest and rapidly growing industries in Malaysia. However, this industry produced large amount of waste known as palm oil mill effluent (POME) which contributes to the pollution of river. It consists of 95 to 96% (v/v) water, 0.6 to 0.7% (v/v) oil and 4 to 5% (w/v) total solids. POME contains high nutrient including metal traces and could promote the growth of bacteria in the water. Consequently, it contributes to oxygen depletion and endangered the aquatic organisms. In this study, 44% (v/v) of glycerol was used as main substrate and 51% (v/v) POME was used as co-substrate and supplement for the growth and itaconic acid production by Aspergillus terreus NRRL 1960. The production medium chosen produced the highest yield based on literature study. To improvise the amount of yield, the Aspergillus terreus spore was immobilized in PVA-alginate-sulfate beads and the fermentation was carried out for 6 days. Fermentation process was done for 0% (w/v) beads for control, 5% (w/v) and 10% (w/v) of beads containing Aspergillus terreus NRRL 1960 spores and 10% (v/v) of free cell of Aspergillus terreus NRRL 1960 that contains 2.071 X 108 spore/mL. The itaconic acid production was highest on the 3rd day of the fermentation. Thus this study shows that immobilization system increased the yield up to 3 folds when the itaconic acid production of 10% (w/v) beads of 9.656 g/L been compared to production of free cells of 3.43 g/L on the 3rd day of fermentation. Besides producing the itaconic acid, immobilized A. terreus also could decolorized the POME. The decolorization process was highest on the 4th day of fermentation, which resulting 42.10% for the 5% beads, 44.15% for the 10% beads and the free cell produced was 65.30%. The reason of high decolorization in free cell is caused by the high growth indicated by biomass produced up to 17.46 g/L compared to only 11.31 g/L and 12.963 g/L for both 5% (w/v) and 10% (w/v) respectively. It can be conclude that as the fungus growth and producing mycelium, the colour causing compounds were bound to mycelium via adsorption that involves a combination of active and passive transport mechanism.